Kohesivitas Pada Kelompok Jamaah Tabligh - Ikbar, Ikbar; Nurrahmi, Febri; Syam, Hamdani M. (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
The Jamaah Tabligh is a very unique group in their dawah efforts involving each member of the group. This study aims to find out how the cohesiveness of such a group by studying the Jamaah Tabligh in Mesjid Cot Goh, Gampong Lamme Garot, Aceh Besar. The theory used in this study is the theory of Groupthink by focusing on the concept of cohesiveness. This study used a descriptive qualitative method. Data collection techniques were carried out using structured interviews on five members of the Tabligh Jamaah and participatory observation. The results showed a high level of individual cohesiveness within the Jamaah Tabligh group measured by four dimensions of cohesiveness including social strength, unity in groups, attractiveness and group collaboration. The cohesiveness was based on the similarity of purpose in da'wah. This cohesiveness has indicated the symptoms of groupthink that appeared in deliberation for decision making in the group.